Efficacy and safety of eltrombopag in the first-line therapy of severe aplastic anemia in children. (6th October 2021) - Jie, Ma; Fu, Lingling; Li, Sidan; He, Yixuan; Yao, Jiafeng; Cheng, Xiaoling; Zhang, Liqiang; Zheng, Jie; Zhang, Rui; Wu, Runhui
Abstract: Eltrombopag is being investigated for the treatment of aplastic anemia (AA) by stimulating hematopoietic stem cell (HSC) proliferation. To evaluate the efficacy and safety of eltrombopag in the first-line therapy of pediatric AA. The present retrospective study assessed pediatric patients with newly diagnosed AA administered immunosuppressive therapy (IST) (rabbit ATG combined with CSA) with eltrombopag at a single center from March to September 2017. All patients were followed up for >2 years. A total of 14 patients (8 males), averagely aged 86 months, were enrolled in this study. Eltrombopag was administered with a median time to initiation of 19.5 days after IST; the median course of treatment was 253 days. Complete and overall response rates at 6 months were 64.3% (9/14 case) and 78.6% (11/14 cases), respectively. The survival rate was 100%, and no relapse occurred in responders. Eltrombopag was well-tolerated; however, the most common adverse events included indirect bilirubin elevation, jaundice, and transient liver-enzyme elevation. By the end of follow-up, bone marrow chromosomes were normal, and no abnormal myelodysplastic syndrome (MDS)-related clones appeared. Addition of eltrombopag to IST is associated with markedly increased complete response with respect to hematology in pediatric patients with SAA compared with a historical cohort, without intolerable side effects.